2011
DOI: 10.1051/0004-6361/201116990
|View full text |Cite
|
Sign up to set email alerts
|

A VLT/FLAMES survey for massive binaries in Westerlund 1

Abstract: Context. There is growing evidence that a treatment of binarity amongst OB stars is essential for a full theory of stellar evolution. However the binary properties of massive stars -frequency, mass ratio & orbital separation -are still poorly constrained. Aims. In order to address this shortcoming we have undertaken a multiepoch spectroscopic study of the stellar population of the young massive cluster Westerlund 1. In this paper we present an investigation into the nature of the dusty Wolf-Rayet star and cand… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 84 publications
(97 reference statements)
1
36
0
Order By: Relevance
“…) and evidence for distinct binary evolutionary channels (e.g. Clark et al 2011b) confirming the predictions of previous theoretical studies (e.g. Petrovic et al 2005).…”
Section: Introductionsupporting
confidence: 87%
“…) and evidence for distinct binary evolutionary channels (e.g. Clark et al 2011b) confirming the predictions of previous theoretical studies (e.g. Petrovic et al 2005).…”
Section: Introductionsupporting
confidence: 87%
“…Building on the evolutionary schemes delineated in Clark et al (2011) we might suppose an additional pathway for close binaries comprising two stars of comparable masses, such that for stars within Wd1 current evolving from the MS (M init ∼ 35−50 M ):…”
Section: Evolutionary Pathways For Massive Stars In Wd1mentioning
confidence: 99%
“…From an observational perspective, after decades of slow progress we have now more than tripled the number of known close binary central stars to more than 40 postcommon envelope systems (Miszalski et al 2011a); we have independently refined the close binary fraction of Bond (2000) to be at least 17±5 % (Miszalski et al 2009a); identified strong tendencies for close binaries to be associated with equatorial rings and fast collimated polar outflows (Miszalski et al 2009b(Miszalski et al , 2011bCorradi et al 2011) and we have identified the binary as the shaping agent in at least 6 systems where the nebula inclination matches the orbital inclination (Jones et al 2011). In addition several efforts are underway to detect binaries of wider separation to finally determine the total binary fraction of PNe, predicted to be higher than expected from the main-sequence binary fraction (Moe & De Marco 2006.…”
Section: And References Therein)mentioning
confidence: 99%
“…Studies of individual massive binary systems are now providing us with ever more accurate parameters of the most massive stars, enabling critical tests for evolutionary models in the upper parts of the HR diagram (Pavlovski & Southworth 2009;Ritchie et al 2009;Ritchie et al 2010;Clark 2011). Record holders include R136, host of the most massive O supergiants , and R145 (Schnurr et al 2009) hosting a hydrogen-rich Wolf-Rayet star for which minimum masses near 100 M have been derived.…”
Section: Massive Binary Evolution (S De Mink)mentioning
confidence: 99%